2018
DOI: 10.1111/tid.13021
|View full text |Cite
|
Sign up to set email alerts
|

Guillain‐Barré syndrome post renal transplant: A systematic review

Abstract: Background Guillain‐Barré syndrome (GBS) is a common ascending polyneuropathy in adults. It is often associated with preceding viral or diarrhoeal illness with cytomegalovirus (CMV), Epstein‐Barr virus (EBV), or Campylobacter jejuni. Solid organ transplant recipients are more susceptible to opportunistic infections with CMV than the general population as a result of immunosuppressive therapies to prevent graft rejection. However, reports of GBS are rare in this population. Objective To systematically review ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…17 Recently, a systematic review analyzing 17 cases of GBS in renal transplant patients identified CMV as the most common trigger for this condition. 18 Generally, patients with CMV-triggered GBS were more likely to show predominantly sensory defects rather than axonal disease, as in our patient's case, revealing specificities of distribution of the target autoantigen related to CMV molecular mimicry. While our patient did not present with a primary CMV infection, he presented with a reactivation of CMV considered as a potential trigger for the neurological autoimmune reaction.…”
Section: Discussionsupporting
confidence: 65%
“…17 Recently, a systematic review analyzing 17 cases of GBS in renal transplant patients identified CMV as the most common trigger for this condition. 18 Generally, patients with CMV-triggered GBS were more likely to show predominantly sensory defects rather than axonal disease, as in our patient's case, revealing specificities of distribution of the target autoantigen related to CMV molecular mimicry. While our patient did not present with a primary CMV infection, he presented with a reactivation of CMV considered as a potential trigger for the neurological autoimmune reaction.…”
Section: Discussionsupporting
confidence: 65%
“…This is higher than the incidence rate of these neuropathies in the general population and of kidney transplant recipients not treated with alemtuzumab. [5][6][7] Secondary autoimmunity after alemtuzumab appears to be mainly B cell driven. A mismatched reconstitution of T and B cells after alemtuzumab can lead to an expansion of B cells in the absence of appropriate T-cell regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of GBS have been reported in bone marrow transplant recipients and are associated with graft versus host disease (GvHD) [19]. In recipients of solid organ transplants, mainly the heart, liver and kidney, GBS usually appears within 1 year after transplantation and is mainly related to CMV infection [2]. According to the patient's CMV and EBV serostatus in the present study, tissue invasion cannot be fully excluded; however, no obvious infectious cause of GBS was found in the performed laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…Among symptoms experienced by renal transplant recipients, those connected with peripheral nerve damage are scarce. Guillain-Barré syndrome (GBS) is the most common acute ascending polyneuropathy in adults, affecting 0.5-2 per 100,000 people per year [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation